2021
DOI: 10.3389/fvets.2021.602622
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic Analysis of Heartworm Preventive Compliance and Revenue in Veterinary Practices in the United States

Abstract: Background: Heartworm disease (HWD) is a potentially fatal condition caused by the nematode Dirofilaria immitis. It is endemic in North America, and the American Heartworm Society recommends that owned dogs be on a Food and Drug Administration-approved HWD preventive year-round. The objective of this study was to compare the 12-month HWD preventive purchase compliance rates of injectable moxidectin (ProHeart® 6) and the dose equivalent in monthly HWD preventives and their associated economic value to the veter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The second and third limitations do not apply to injectable HW prevention that is restricted to the use by or on the order of a licensed veterinarian [7,8], but cannot be ruled out for MHWP. Despite this, retrospective analyses of transaction data have been used previously to examine purchase compliance with antiparasitics in dogs [6,11,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second and third limitations do not apply to injectable HW prevention that is restricted to the use by or on the order of a licensed veterinarian [7,8], but cannot be ruled out for MHWP. Despite this, retrospective analyses of transaction data have been used previously to examine purchase compliance with antiparasitics in dogs [6,11,[13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…We did not include an economic calculation in the first analysis, as the revenue benefits of implementing PH6 and PH12 as a strategy to prevent HW disease have been demonstrated previously in two retrospective analyses of transaction data [6,16]. A pharmacoeconomic analysis evaluated the impact of incorporating PH6 into the practice formulary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compliance amongst monthly heartworm preventive patients did not increase in this study year over year. A similar study based on Australian data found that Single-year compliance with ProHeart SR-12 was 92.8–96.9% vs. 26.9–36.5% for dogs receiving MHWP products and multiple year compliance was 76.7% for ProHeart SR-12 and 24.4% for MHWP medications [ 9 ]. Australia has a lower age of first use for injectable moxidectin (12 weeks), compared to the US, where PH 12 is approved for use in dogs 1 year of age and older.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to concerns of veterinary applications of doxycycline, in companion animals, such as long treatment timeframes, dysbiosis side-effects, and antibiotic stewardship of a human essential medicine, development of short-course, narrow-spectrum anti-Wolbachia heartworm therapeutics without general antibiotic properties, may offer a potential future alternative [13]. ML preventatives, costing typically between $266-329 a year for a pet's treatment in the USA, represent a potential multi-billion dollar global market [14]. Due to emergent spread of Dirofilaria immitis infections, the growing concerns of ML prophylactic failure in USA and the current inadequacies of curative treatments, new therapeutic strategies are being intensively investigated.…”
Section: Introductionmentioning
confidence: 99%